Pengaruh Likuiditas, Leverage, Profitabilitas, dan Ukuran Perusahaan terhadap Financial Distress di Sektor Trade, Service, and Invesment - Hasivatus Sariroh (Jurnal Ilmu Manajemen, 2021)
This study is a quantitative study that aims to determine the effect of the current ratio, debt to asset ratio, return on assets, and firm size on financial distress. Logistic regression method was used to test all relationships between independent variables and dependent variables with nominal/ordinal data scales. The dependent variable in this study is financial distress. The independent variables in this study are liquidity, leverage, profitability and firm size. This study uses secondary data from annual reports of trading, service, and investment companies listed on the Indonesia Stock Exchange from 2016 to 2018. The population used is companies in the trade, services, and investment sectors listed on the Indonesia Stock Exchange (IDX). from 2016 to 2018 with a total of 162 companies selected using purposive sampling technique. The results of hypothesis testing indicate that the current ratio, debt to asset ratio, return on assets, and firm size have no effect on the company's financial distress. From research conducted by researchers, for management to be used as a basis to take corrective actions if there are indications that the company experiencing financial distress. For investors, to be used as a basis in making the right decision to invest in a company.